An mHealth-based school health education system designed to scale up salt reduction in China (EduSaltS): A development and preliminary implementation study - Zhang, Puhong; Sun, Jingwen; Li, Yinghua; Li, Yuan; Sun, Yuewen; Luo, Rong; Nie, Xueqiong; Li, Li; Liu, Yu; He, Feng J (Frontiers in Nutrition, 2023)
Background High-salt diet is an important risk factor for several non-communicable diseases. School-based health education has been found effective in reducing salt intake among children and their families in China. However, no such interventions have been scaled up in the real world. For this purpose, a study was launched to support the development and scale-up of an mHealth-based system (EduSaltS) that integrated routine health education and salt reduction and was delivered through primary schools. This study aims to elaborate the framework, development process, features, and preliminary scaling-up of the EduSaltS system. Methods The EduSaltS system evolved from previously successfully tested interventions to reduce family salt intake by empowering schoolchildren through school health education. EduSaltS was designed by following the WHO’s conceptual framework for developing a scaling-up strategy which accounted for the nature of the innovation, the capacity of the implementing organizations, the characteristics of the environment, the resources available, and type of scaling up. The system was then developed step by step from determination of online platform architecture, definition of component interventions and activities, development of specific educational materials and tools, to the development of the online/offline hybridized system. The system was tested and refined by a pilot in two schools and a preliminary scale-up in two cities in China. Results EduSaltS was developed as an innovative health education system, including an online WeChat-based education platform, a set of offline activities, and an actual administrative website showing the progress and setting the system. The WeChat platform could be installed on users’ smartphones to automatically deliver 20 sessions of five-minute well-structured cartoon video classes, followed by other online interactive activities. It also helps support project implementation and real-time performance evaluation. As a first-stage roll-out, a one-year course has been successfully implemented among 54,538 children and their families from 209 schools in two cities, and the average course completion rate was 89.1%. Conclusion As an innovative mHealth-based health education system, EduSaltS was developed based on successfully tested interventions and an appropriate framework for scaling up. The early-stage roll-out has shown its preliminary scalability, and further evaluation is ongoing.